2005
DOI: 10.1536/ihj.46.289
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Injection of Fibroblast Growth Factor-2 Plus Heparin Suppresses Cardiac Failure Progression in Rats With Hypertensive Heart Disease

Abstract: SUMMARYA reduction of coronary flow reserve has been reported in patients with hypertensive heart disease (HHD), which suggests that myocardial ischemia may contribute to the progression to cardiac failure in HHD. Therefore, we evaluated whether fibroblast growth factor (FGF)-2 and/or heparin, which induce angiogenesis, may affect cardiac function in the setting of HHD.We used Dahl salt sensitive (DS) rats as an HHD model. Direct intramyocardial injection of 100 µg of FGF-2 plus 1.28 µg of heparin (n = 6), 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Studies also revealed differential effects of high and low molecular weight isoforms of FGF2 on cardiac hypertrophy, fibrosis and inflammation (143). Intramyocardial injection of FGF2 (plus heparin) in rats with hypertension-induced cardiac hypertrophy was associated with significant improvements in systolic pump function and ventricular dilation, as well as increased myocardial capillary density (144). Other members of the FGF growth factor family (e.g., acidic FGF or FGF1) may also promote angiogenesis (145) and have been shown to be overexpressed in hearts of patients with dilated cardiomyopathy (146), but their role in cardiac hypertrophy has not been directly examined experimentally.…”
Section: Growth Factor Signaling Involved In the Regulation Cardiac Amentioning
confidence: 99%
“…Studies also revealed differential effects of high and low molecular weight isoforms of FGF2 on cardiac hypertrophy, fibrosis and inflammation (143). Intramyocardial injection of FGF2 (plus heparin) in rats with hypertension-induced cardiac hypertrophy was associated with significant improvements in systolic pump function and ventricular dilation, as well as increased myocardial capillary density (144). Other members of the FGF growth factor family (e.g., acidic FGF or FGF1) may also promote angiogenesis (145) and have been shown to be overexpressed in hearts of patients with dilated cardiomyopathy (146), but their role in cardiac hypertrophy has not been directly examined experimentally.…”
Section: Growth Factor Signaling Involved In the Regulation Cardiac Amentioning
confidence: 99%
“…Our colleagues demonstrated that a single intramyocardial injection of bFGF induces an increase in capillary and arteriolar density, which subsequently suppresses the progression of cardiac failure in Dahl salt-sensitive rats with hypertensive heart disease (HHD) [4]. Hypertension contributes to left ventricular hypertrophy (LVH) and plays an etiological role in left ventricular remodeling [5], which involves disruption of the supporting structure, cell slippage, myocyte hypertrophy, and interstitial fibrosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…FGF-2 is processed into its mature form by truncation of 9 amino acids at the NH2-terminal (MAASGITSLPALPEDGG,), and there is another putative truncation site for DPP-4 following PALPEDGG,. It was reported that FGF-2 has a cardioprotective role by promoting angiogenesis in cardiac tissue [ 45 ], suggesting that suppression of FGF-2-induced angiogenesis by DPP-4 may be one of the pathologic changes mediated by this molecule.…”
Section: Discussionmentioning
confidence: 99%